On the Chattering of SARSA with Linear Function Approximation - Zhang, Shangtong; Laroche, Romain; Tachet des Combes, Remi (arXiv, 2022)
SARSA, a classical on-policy control algorithm for reinforcement learning, is known to chatter when combined with linear function approximation: SARSA does not diverge but oscillates in a bounded region. However, little is know about how fast SARSA converges to that region and how large the region is. In this paper, we make progress towards solving this open problem by showing the convergence rate of projected SARSA to a bounded region. Importantly, the region is much smaller than the ball used for projection provided that the the magnitude of the reward is not too large. Our analysis applies to expected SARSA as well as SARSA(λ). Existing works regarding the convergence of linear SARSA to a fixed point all require the Lipschitz constant of SARSA's policy improvement operator to be sufficiently small; our analysis instead applies to arbitrary Lipschitz constants and thus characterizes the behavior of linear SARSA for a new regime.